Internet and Network Economics 6th International Workshop, WINE 2010, Stanford, CA, USA, December 13-17, 2010, Proceedings - Saberi, Amin (Theoretical Computer Science and General Issues,, 2010)
This book constitutes the refereed proceedings of the 6th International Workshop on Internet and Network Economics, WINE 2010, held in Stanford, USA, in December 2010. The 52 revised full papers presented were carefully reviewed and selected from 95 submissions. The papers are organized in 33 regular papers and 19 short papers.